2010
DOI: 10.2223/jped.2010
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting early discontinuation of exclusive breastfeeding in the first month of life

Abstract: Objective: To investigate factors associated with discontinuation of exclusive breastfeeding in the first month of lactation, in the city of Feira de Santana, Brazil. Methods: Cohort study with follow-up of 1,309 mother-child pairs selected from all maternities in the municipality. Data were collected in hospital and in home visits during the first month of life. Logistic regression analysis was used to examine the relationship between outcome and variables of interest. Results: Lack of prior breastfeeding exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 12 publications
1
17
1
11
Order By: Relevance
“…Há alguns anos, foi descrito o fenômeno da "confusão de bicos", em que a criança em uso de bicos artificiais diminui a eficiência da sucção no seio, reduzindo a produção do leite e aumentando a chance da oferta precoce de alimentos pela mãe 19 . Alguns estudos nacionais já descreveram associação entre o uso da chupeta e a interrupção precoce do aleitamento materno exclusivo [20][21][22][23] . O delineamento transversal do presente estudo, no entanto, limita o estabelecimento de relação causal.…”
Section: I S C U S S ã Ounclassified
“…Há alguns anos, foi descrito o fenômeno da "confusão de bicos", em que a criança em uso de bicos artificiais diminui a eficiência da sucção no seio, reduzindo a produção do leite e aumentando a chance da oferta precoce de alimentos pela mãe 19 . Alguns estudos nacionais já descreveram associação entre o uso da chupeta e a interrupção precoce do aleitamento materno exclusivo [20][21][22][23] . O delineamento transversal do presente estudo, no entanto, limita o estabelecimento de relação causal.…”
Section: I S C U S S ã Ounclassified
“…Such finding was also evoked by Gatti, indicating that the perception of inadequate milk supply is put forth by mothers as the main reason for breastfeeding discontinuation during the first four weeks after delivery and also the most common reason for early cessation [32] and total cessation of breastfeeding [33]. As far as sucking difficulty is concerned, it has been reported that cracked nipples are one of the four variables assessed and associated with an early discontinuation of EB [34].…”
Section: Discussionmentioning
confidence: 74%
“…De fato, estudo brasileiro com recém-nascidos normais detectou que medidas de prevenção minimizariam a interrupção do aleitamento exclusivo no 1º mês de vida 30 . Essas medidas, acrescidas de seguimento longitudinal até o estabelecimento da técnica de alimentação e outros recursos necessários às peculiaridades de cada lactente com FOT, permitiriam ganho de peso apropriado.…”
Section: Resultsunclassified
“…Adotou-se um nível de significância de 5% (p ≤ 0,05). Quanto à época do diagnóstico, em 75,3% (162) dos casos, a fenda foi diagnosticada após o nascimento, ainda na maternidade; em 14% (30), no exame pré-natal; e em 10,2% (22), após a alta da maternidade. A análise dos dados demonstrou diferença significativa entre a época do diagnóstico e o tipo de fenda (p < 0,0001) (Tabela 2).…”
Section: Métodounclassified